A total heat exchange membrane and its preparation method and application

CN122894871APending Publication Date: 2026-10-13GUANGDONG KINGFA MEDICAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610739448.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-27
Publication Date
2026-10-13

AI Technical Summary

Benefits of technology

本发明的全热交换膜兼顾了良好的透湿性和气体阻隔性、抗菌性能良好,且经过多次湿热循环后,全热交换膜的透湿性和气体阻隔性保持良好,抗菌性能也保持良好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to a kind of total heat exchange film and its preparation method and application.The total heat exchange film includes porous support film and active layer loaded on the surface of the porous support film.The total heat exchange film of the present application has good moisture permeability and gas barrier property, good antibacterial performance, and after multiple wet heat cycles, the moisture permeability and gas barrier property of the total heat exchange film remain good, and the antibacterial performance also remains good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of heat exchanger technology, and more specifically, to a total heat exchange membrane, its preparation method, and its application. Background Technology

[0002] The total heat exchange membrane is the core component of a total heat exchanger, and its performance directly determines the energy recovery efficiency. The active layer of traditional total heat exchange membranes is often made of a single polyvinyl alcohol or chitosan. Such single-component active layers are difficult to simultaneously achieve good moisture permeability and gas barrier properties.

[0003] Furthermore, when the total heat exchange membrane is used in high-heat and high-humidity or alternating hot and humid environments for a long time, the active layer may age or components may detach, which may result in poor moisture permeability and / or gas barrier performance.

[0004] Furthermore, the operating environment of total heat exchange membranes is prone to harboring bacteria, and the humid and hot environment is conducive to bacterial growth. Therefore, total heat exchange membranes usually need to have good antibacterial properties. To meet this requirement, existing technologies mainly add nano-metals or nano-metal oxides with bactericidal effects to the active layer. However, these usually only have good bactericidal effects in the initial stage of use, and their bactericidal effect will be greatly reduced once the humid and hot environment is handled for a long time. Summary of the Invention

[0005] The primary objective of this invention is to overcome the problems in the prior art where total heat exchange membranes cannot simultaneously achieve good moisture permeability and gas barrier properties, and where moisture permeability, gas barrier properties, and antibacterial properties significantly decrease after prolonged use in humid and hot environments, and to provide a total heat exchange membrane.

[0006] A further objective of this invention is to provide a method for preparing a total heat exchange membrane.

[0007] A further object of the present invention is to provide a total heat exchange membrane.

[0008] The above-mentioned objective of this invention is achieved through the following technical solution: A total heat exchange membrane includes a porous support membrane and an active layer loaded on the surface of the porous support membrane; By weight, the active layer comprises the following components: 0.8-2 parts polyvinyl alcohol, 0.2-0.6 parts alginate, 0.1-0.25 parts crosslinking agent, 1.6-4 parts chitosan, 0.3-1.3 parts calcium salt, 0.8-1.6 parts hygroscopic agent, 0.08-0.32 parts antibacterial agent, and 0.16-0.48 parts nano silica; The water contact angle of the surface of the porous support membrane is ≤78°.

[0009] This invention adds a hygroscopic agent and an antibacterial agent to the active layer of the total heat exchange membrane, so that the total heat exchange membrane has certain moisture permeability and good antibacterial properties.

[0010] The inventors of this invention have discovered that by adjusting the mass ratio of polyvinyl alcohol and chitosan in the active layer of the total heat exchange membrane, the hydrophilicity and density of the active layer can be balanced, so that the total heat exchange membrane can have good moisture permeability and gas barrier properties to a certain extent, while also giving the active layer good mechanical properties and stability, so that the various properties of the total heat exchange membrane remain good after wet heat treatment.

[0011] Further research by the inventors revealed that the addition of nano-silica can act as a "molecular sieve" structure in the active layer, allowing water molecules to pass through while blocking gas molecules, thereby further enhancing the synergistic effect of moisture permeability and gas barrier properties.

[0012] Further research by the inventors revealed that adding alginate and calcium salt further enhances the gas barrier properties of the total heat exchange membrane. Alginate not only acts as a thickener with hygroscopic properties but also crosslinks with calcium salt and forms hydrogen bonds with polyvinyl alcohol, creating an interpenetrating network and improving the stability of the active layer. This results in improved gas barrier properties after hygroscopic heat treatment, and the membrane maintains good moisture permeability and antibacterial properties because the antibacterial agent and nano-silica do not significantly detach or aggregate. Calcium salt not only has hygroscopic properties but its calcium ions can also crosslink with alginate, further enhancing the crosslinking degree and stability of the active layer. This further improves the gas barrier properties of the total heat exchange membrane, and the membrane maintains good gas barrier properties, moisture permeability, and antibacterial properties after hygroscopic heat treatment.

[0013] The water contact angle on the surface of the porous support membrane is also crucial. Controlling it within a certain range is beneficial for the porous support membrane to bond well with the active layer, so that the gas barrier performance, moisture permeability and antibacterial performance of the total heat exchange membrane are maintained well after wet heat treatment.

[0014] The total heat exchange membrane of the present invention achieves good moisture permeability and gas barrier properties, as well as good antibacterial properties, by adjusting the water contact angle of the porous support membrane surface within a specific range and coordinating the components in the active layer. After multiple wet and heat cycles, the total heat exchange membrane maintains good moisture permeability and gas barrier properties, and also maintains good antibacterial properties.

[0015] In this invention, the water contact angle of the porous support membrane surface can be measured using an optical contact angle measuring instrument in accordance with GB / T 30693-2014 "Measurement of Water Contact Angle of Plastic Film".

[0016] In this invention, the amount of polyvinyl alcohol in the active layer can specifically be 0.8, 0.9, 1.0, 1.2, 1.4, 1.6, 1.8, or 2.0 parts by weight, or a range formed by any two of the above values; the amount of alginate can specifically be 0.2, 0.3, 0.4, 0.5, or 0.6 parts by weight, or a range formed by any two of the above values; and the amount of crosslinking agent can specifically be 0.10, 0.12, 0.15, or 0.1 parts by weight. 8, 0.20, 0.22, 0.24, 0.25 parts by weight, or any two of the above values ​​within a range; the specific amount of chitosan can be 1.6, 1.8, 2.0, 2.2, 2.5, 2.8, 3.0, 3.2, 3.5, 3.8, 4.0 parts by weight, or any two of the above values ​​within a range; the specific amount of calcium salt can be 0.30, 0.32, 0.40, 0.50, 0.60, 0.70 parts by weight. The dosage of the desiccant can be 0.8, 0.9, 1.0, 1.10, 1.2, 1.28, or 1.30 parts by weight, or a range formed by any two of the above values; the dosage of the desiccant can be 0.8, 0.9, 1.0, 1.2, 1.4, or 1.6 parts by weight, or a range formed by any two of the above values; the dosage of the antibacterial agent can be 0.08, 0.09, 0.10, 0.12, 0.15, 0.18, or 0.2 parts by weight. 0, 0.22, 0.25, 0.28, 0.30, 0.32 parts by weight or any two of the above values; the specific amount of nano-silica can be 0.16, 0.17, 0.18, 0.20, 0.22, 0.25, 0.28, 0.30, 0.32, 0.35, 0.38, 0.40, 0.42, 0.45, 0.48 parts by weight or any two of the above values.

[0017] The water contact angle of the porous support membrane surface can be 55°, 58°, 60°, 62°, 65°, 68°, 70°, 72°, 74°, 76°, 78° or any two of the above values ​​within a range.

[0018] Preferably, the thickness of the porous support membrane is 10-20 micrometers.

[0019] Preferably, the porous support membrane can be made of one of the following materials: polypropylene, polyethylene, polyamide, polytetrafluoroethylene, and polyvinylidene fluoride.

[0020] Preferably, the porosity of the porous support membrane is 30-50%.

[0021] Preferably, the average pore size of the porous support membrane is 0.1~0.5μm.

[0022] Porous support membranes can be purchased commercially or made at home.

[0023] The process of making it in-house can be achieved by hydrophilically treating an existing porous support membrane.

[0024] Optionally, the hydrophilic treatment method can be at least one of hydrogen peroxide ultrasonic oxidation or plasma treatment.

[0025] Optionally, the process of ultrasonic oxidation with hydrogen peroxide is as follows: the porous support membrane is placed in a mixed solution of hydrogen peroxide and ethanol and ultrasonically treated at 25~40℃ for 5~30 minutes.

[0026] Optionally, the plasma treatment power is 200~400W and the time is 30~90s.

[0027] Optionally, the volume ratio of hydrogen peroxide to ethanol is 1:(3~5).

[0028] Optionally, the volume fraction of the hydrogen peroxide is 2-6%.

[0029] Preferably, the thickness of the active layer is 1 to 5 micrometers.

[0030] Preferably, the viscosity-average molecular weight of the polyvinyl alcohol is 50,000 to 200,000.

[0031] Preferably, the viscosity-average molecular weight of the polyvinyl alcohol can be determined by gel permeation chromatography.

[0032] Preferably, the alginate is at least one of sodium alginate, potassium alginate, and calcium alginate.

[0033] Preferably, the viscosity of the alginate is 10~1500 mPa·s.

[0034] More preferably, the viscosity of the alginate is 15~250 mPa·s.

[0035] In this invention, the viscosity of alginate can be measured by a rotational viscometer at 25°C, with deionized water as the solvent and a concentration of 1 wt%.

[0036] Preferably, the weight-average molecular weight of the chitosan is 50,000 to 400,000.

[0037] In this invention, the weight-average molecular weight of chitosan can be determined by gel chromatography.

[0038] Commonly used crosslinking agents in this field can be used in this invention.

[0039] Preferably, the crosslinking agent is at least one selected from glutaraldehyde, glyoxal, maleic acid, malic acid, and polyethylene glycol diglycidyl ether.

[0040] Preferably, the mass ratio of the alginate to the crosslinking agent is (8~11):(3~6).

[0041] Commonly used calcium salts in this field can be used in this invention.

[0042] Preferably, the calcium salt is at least one of calcium halide, calcium nitrate, calcium lactate, or calcium gluconate.

[0043] More preferably, the calcium halide is at least one of calcium chloride or calcium bromide.

[0044] Commonly used antibacterial agents in this field can be used in this invention.

[0045] Preferably, the antibacterial agent is at least one of zinc oxide or elemental silver.

[0046] Preferably, the average particle size of the antibacterial agent is in the nanometer range.

[0047] Preferably, the average particle size of the antibacterial agent is 20-80 nm.

[0048] In this invention, the average particle size of the antibacterial agent can be measured by electric microscopy.

[0049] Preferably, the average particle size of the nano-silica is 10~50nm.

[0050] More preferably, the average particle size of the nano-silica is 11~16nm.

[0051] In this invention, the average particle size of nano-silica can be measured by electrical microscopy.

[0052] Preferably, the surface of the nano-silica is modified with a silane coupling agent.

[0053] More preferably, the silane coupling agent is at least one selected from γ-aminopropyltriethoxysilane, N-β-aminoethyl-γ-aminopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, and mercaptopropyltrimethoxysilane.

[0054] More preferably, the process of surface-modifying the nano-silica with a silane coupling agent is as follows: mixing the nano-silica with a solution of the silane coupling agent, sonicating, filtering, and drying.

[0055] More preferably, the solution of the silane coupling agent is an ethanol solution of the silane coupling agent.

[0056] More preferably, the concentration of the silane coupling agent in the solution is 0.5~3wt%.

[0057] Commonly used hygroscopic agents in this field can be used in this invention.

[0058] Preferably, the hygroscopic agent is at least one of lithium chloride, zinc chloride, and nano-montmorillonite.

[0059] Preferably, the thickness of the active layer is 1~5μm.

[0060] Preferably, the active layer further includes 1.2 to 2.4 parts of a pH adjuster.

[0061] More preferably, the pH adjuster is at least one of acetic acid, lactic acid, citric acid, formic acid, and propionic acid.

[0062] Preferably, the active layer is formed by drying the casting solution.

[0063] More preferably, the casting solution is obtained by mixing a polyvinyl alcohol composite solution and a chitosan composite solution, or by mixing the components of the active layer with water.

[0064] The casting solution is obtained by mixing a polyvinyl alcohol composite solution and a chitosan composite solution. The resulting total heat exchange membrane has better moisture permeability and gas barrier properties. After multiple wet and heat cycles, the moisture permeability and gas barrier properties of the total heat exchange membrane can also be maintained better.

[0065] More preferably, the mass ratio of the polyvinyl alcohol composite solution to the chitosan composite solution is (12~25):(75~88).

[0066] More preferably, the polyvinyl alcohol composite solution comprises the following components in parts by weight: 4-10 parts polyvinyl alcohol, 1-3 parts sodium alginate, 0.5-1.2 parts crosslinking agent, and 85-93 parts water; More preferably, the chitosan composite solution comprises the following components in parts by weight: 2-5 parts chitosan, 0.4-1.6 parts calcium salt, 1.0-2.0 parts hygroscopic agent, 0.1-0.4 parts antibacterial agent, 0.2-0.6 parts nano silica, and 91.4-95.3 parts acidic aqueous solution.

[0067] More preferably, the pH of the acidic aqueous solution is 2 to 3.

[0068] More preferably, the acidic aqueous solution is an aqueous solution of an organic acid.

[0069] More preferably, the organic acid aqueous solution is at least one selected from acetic acid aqueous solution, lactic acid aqueous solution, citric acid aqueous solution, formic acid aqueous solution, and propionic acid aqueous solution.

[0070] The preparation method of the above-mentioned total heat exchange membrane includes the following steps: The components of the active layer are prepared into a casting solution, which is then coated onto the surface of a porous support membrane and dried to form the active layer, thus obtaining the total heat exchange membrane.

[0071] Preferably, polyvinyl alcohol, sodium alginate and crosslinking agent are first prepared into a polyvinyl alcohol composite solution, and chitosan, calcium salt, hygroscopic agent, antibacterial agent and nano silica are prepared into a chitosan composite solution. The polyvinyl alcohol composite solution and the chitosan composite solution are then mixed into a casting solution. The casting solution is coated on the surface of a porous support membrane and dried to form an active layer, thus obtaining the total heat exchange membrane.

[0072] Preferably, the drying process is as follows: first, keep warm at 25~35℃ for 3~10 minutes, and then keep warm at 50~70℃ for 5~15 minutes.

[0073] The application of the above-mentioned total heat exchange membrane in the preparation of total heat exchangers is also within the scope of protection of this invention.

[0074] A total heat exchanger includes the aforementioned total heat exchange membrane.

[0075] Compared with the prior art, the beneficial effects of the present invention are: The total heat exchange membrane of the present invention has good moisture permeability and gas barrier properties, good antibacterial properties, and after multiple wet heat cycles, the moisture permeability and gas barrier properties of the total heat exchange membrane are maintained, as are the antibacterial properties. Detailed Implementation

[0076] To more clearly and completely describe the technical solution of the present invention, the present invention will be further described in detail below through specific embodiments. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the present invention. Various changes can be made within the scope of the claims of the present invention.

[0077] The reagents used in the various embodiments and comparative examples of this invention are described below: Porous Support Membrane A: PP microporous membrane, thickness 16μm, surface water contact angle 89°, YCH-JS-16, Shenzhen Yuanchenghui Electronics Co., Ltd., porosity 43%, average pore size 0.2μm; Porous Support Membrane B: PE microporous membrane, thickness 16μm, surface water contact angle 88°, YCH-PE16, Shenzhen Yuanchenghui Electronics Co., Ltd., porosity 40%, average pore size 0.21μm; Porous support membrane 1#: The water contact angle on the surface is 65°. It is self-made and the process is as follows: The porous support membrane A is placed in a mixed solution of hydrogen peroxide and anhydrous ethanol with a volume fraction of 4% (the volume ratio of hydrogen peroxide to anhydrous ethanol is 1:4). It is ultrasonically treated at 40°C for 15 minutes. After taking it out, it is rinsed with deionized water until neutral and dried at 60°C. Porous support membrane 2#: The water contact angle on the surface is 60°. It is self-made. The process is different from that of porous support membrane 1# in that the ultrasonic treatment time is 30 minutes. Porous support membrane #3: The water contact angle on the surface is 70°. It is self-made. The process is different from that of porous support membrane #1 in that the ultrasonic treatment temperature is 25°C and the ultrasonic treatment time is 5 minutes. Porous support membrane #4: The water contact angle on the surface is 60°. It is self-made. The process is as follows: The porous support membrane B is subjected to plasma treatment with a power of 300W and a treatment time of 60s. Polyvinyl alcohol 1#: Grade: P868683, Purchaser: Beijing Innocare Technology Co., Ltd., Viscosity-average molecular weight: 120,000; Polyvinyl alcohol 2#: Grade: P105126, Purchaser: Beijing Innocare Technology Co., Ltd., Viscosity-average molecular weight: 80,000; Sodium alginate #1: Grade: A02570, Purchased from: Beijing Innocare Technology Co., Ltd., Viscosity: 200 mPa·s; Sodium alginate #2: Grade: V31240, Purchased from: Beijing Innocare Technology Co., Ltd., Viscosity: 700 mPa.s; Sodium alginate #3: Grade: 89186K, Purchased from: Beijing Innocare Technology Co., Ltd., Viscosity: 20 mPa.s; Sodium carboxymethyl cellulose: Grade: A76272, Purchased from: Beijing Innocare Technology Co., Ltd., Viscosity: 600 mPa·s; Crosslinking agent: glutaraldehyde, commercially available; Chitosan 1#: Brand: CTS-100, Purchased by: Zhejiang Jinke Pharmaceutical Co., Ltd., Weight-average molecular weight is 240,000; Chitosan 2#: Brand: LZ-150, Purchased by: Shandong Aokete, Weight-average molecular weight: 200,000; Calcium salt: Anhydrous calcium chloride, commercially available; Zinc salt: Anhydrous zinc chloride, commercially available; Desiccant: Anhydrous lithium chloride, commercially available; Antibacterial agent: It is obtained by mixing nano zinc oxide and nano silver in a mass ratio of 2:1; wherein: nano zinc oxide has an average particle size of 40nm, grade: XY-NZ30, and is purchased from Shandong Xingya New Materials; nano silver has an average particle size of 40nm, grade: JCSNP-995-50, and is purchased from Nanjing Jicang Nano. Nano silica #1: Average particle size is 15nm, brand name: AEROSIL 200, manufacturer: Evonik AEROSIL; Nano silica #2: Average particle size is 12nm, grade: CY-SP15, manufacturer: Zhejiang Jiupeng; Nano silica #3: average particle size 25nm, HN-SQ15, Hangzhou Hengna; Micron-sized silica: average particle size 5μm, LR-S105, Jiangsu Lianrui; Montmorillonite: Nano-montmorillonite with an average particle size of 40 nm; The aforementioned nano-silica, micron-sized silica, or montmorillonite are all modified with silane coupling agents before use. The modification process is as follows: mix nano-silica, micron-sized silica, or montmorillonite with a 1wt% KH-550 ethanol solution, sonicate for 30 minutes, filter, dry, and set aside. pH adjuster: Acetic acid, commercially available; Unless otherwise specified, all components (e.g., crosslinking agents, hygroscopic agents, pH adjusters, etc.) used in each parallel embodiment and comparative example are the same commercially available products.

[0078] Examples 1-15 and Comparative Examples 1-12 Examples 1-15 and Comparative Examples 1-12 provide a series of total heat exchange membranes, each comprising a porous support membrane and an active layer loaded on the surface of the porous support membrane. The active layer has a thickness of 2 μm. The selection or composition of the porous support membrane and the active layer are shown in Tables 1-4.

[0079] The preparation methods of the total heat exchange membranes in each embodiment and comparative example include the following steps: 1) Preparation of polyvinyl alcohol composite solution 1.1) Add deionized water to the reactor, heat to 80°C, add polyvinyl alcohol, and stir magnetically for 30 minutes; 1.2) Add sodium alginate (if any) and sodium carboxymethyl cellulose (if any) in sequence, and continue stirring for 30 minutes; 1.3) Add the crosslinking agent at a rate of 1 drop / second. After the addition is complete, continue stirring for 60 minutes and cool to room temperature to obtain the polyvinyl alcohol composite solution. 2) Preparation of chitosan composite solution 2.1) Add pH adjuster to deionized water to obtain acetic acid solution with pH 2.5, add chitosan, and stir magnetically for 10 min to obtain dilute chitosan solution; 2.2) Add calcium salt (if any) and zinc salt (if any) hygroscopic agents to the dilute chitosan solution and stir until dissolved; 2.3) Add antibacterial agent and nano silica (if any), micro silica (if any), montmorillonite (if any), ultrasonically disperse for 20 min and then magnetically stir for 10 min to obtain chitosan composite solution; 3) Preparation of casting solution The polyvinyl alcohol composite solution and the chitosan composite solution were mixed and placed on a magnetic stirrer. The mixture was stirred for 30 minutes at a speed of 300 r / min to obtain the casting solution. 4) Coating and drying A coating process is used to apply the casting solution to the surface of the porous support membrane, and the coating thickness is controlled. Then, it is placed in a drying oven and dried at 30°C for 5 minutes, and then heated to 60°C for 10 minutes. The thickness of the active layer formed after drying is 2 micrometers, which is the total heat exchange membrane.

[0080] Table 1

[0081] Table 2

[0082] Example 16 Example 16 provides a total heat exchange membrane, which differs from Example 1 in that the thickness of the active layer is 3 μm.

[0083] The difference between the preparation method of the total heat exchange membrane in this embodiment and that in Example 1 is that in step 4), the thickness of the active layer formed after drying is 3 micrometers.

[0084] Example 17 Example 17 provides a total heat exchange membrane, which includes a porous support membrane and an active layer loaded on the surface of the porous support membrane. The thickness of the active layer is 2 μm. The porous support membrane is porous support membrane 1#. The active layer includes the following components: 1.6 parts by weight of polyvinyl alcohol 1#, 0.4 parts by weight of sodium alginate 1#, 0.6 parts by weight of crosslinking agent 1#, 2.4 parts by weight of chitosan 1#, 0.48 parts by weight of calcium salt, 1.28 parts by weight of hygroscopic agent, 0.12 parts by weight of antibacterial agent, and 0.32 parts by weight of nano silica 1#.

[0085] The preparation method of the total heat exchange membrane in this embodiment includes the following steps: 1) Weigh out 1.6 parts by weight of polyvinyl alcohol 1#, 0.4 parts by weight of sodium alginate 1#, 0.6 parts by weight of crosslinking agent 1#, 2.4 parts by weight of chitosan 1#, 0.48 parts by weight of calcium salt, 1.28 parts by weight of hygroscopic agent, 0.12 parts by weight of antibacterial agent, 0.32 parts by weight of nano silica 1#, and 92.8 parts by weight of acetic acid solution with pH 2.5; 2) Add chitosan to the acetic acid solution and stir magnetically for 10 min. Then add calcium salt and desiccant and stir until dissolved. Add antibacterial agent and nano silica, sonicate for 20 min and stir magnetically for 10 min to obtain mixture A. 3) Add polyvinyl alcohol to mixture A and stir magnetically for 30 minutes under constant temperature water bath at 80 degrees Celsius; then add crosslinking agent dropwise at a rate of 1 drop / second. After the addition is complete, continue stirring for 60 minutes and cool to room temperature to obtain casting solution. 4) Coating and drying A coating process is used to apply the casting solution to the surface of the porous support membrane, and the coating thickness is controlled. Then, it is placed in a drying oven and dried at 30°C for 5 minutes, and then heated to 60°C for 10 minutes. The thickness of the active layer formed after drying is 2 micrometers, which is the total heat exchange membrane.

[0086] Table 3

[0087] Table 4

[0088] Performance testing The performance of the total heat exchange membranes in each embodiment and comparative example was tested according to the following method.

[0089] (1) Moisture permeability: The test was conducted using the cup-type moisture absorption method according to the standard GB / T 1037-2021. The test temperature was 38℃ and the relative humidity was 90%RH. The unit of the test result is g / m²·24h.

[0090] (2) Gas barrier index: Determined according to ISO 5636.5:2003 standard, the time required for 100 mL of dry air to pass through a 6.45 cm² effective area sample under a constant pressure difference of 1.22 kPa is measured and expressed as the gas barrier index. The gas barrier index is read by a diaphragm permeability meter, and the unit of the test result is s / (in). 2 ·100cc·1.22kPa).

[0091] (3) Antibacterial rate: The antibacterial rate was tested according to the standard JIS Z 2801:2010. The test strain was Staphylococcus aureus, and the culture conditions were freeze-dried bacteria cultured at 35℃ for 20h, with a final concentration of 2×10⁻⁶. 5 CFU / mL.

[0092] (4) Performance after damp heat cycling: The total heat exchange membrane was treated at 60℃ and 80%RH for 172 hours, and then the moisture permeability, air barrier index and antibacterial rate after damp heat cycling were measured according to methods (1), (2) and (3). The retention rate was calculated by comparing the initial moisture permeability, air barrier index and antibacterial rate (without damp heat aging) with the moisture permeability, air barrier index and antibacterial rate after damp heat cycling. a) Moisture permeability retention rate after hydrothermal cycling = (Moisture permeability after hydrothermal cycling / Initial moisture permeability) × 100%; b) Retention rate of air resistance index after wet-heat cycling = (Air resistance index after wet-heat cycling / Initial air resistance index) × 100%; c) Antimicrobial retention rate after moist heat cycling = (antimicrobial retention rate after moist heat cycling / initial air barrier index) × 100%.

[0093] The performance test results of each embodiment and comparative example are shown in Table 5.

[0094] Table 5

[0095] As can be seen from Table 5: The moisture permeability of the total heat exchange membranes in Examples 1-17 is ≥10.0×10⁻⁶. 3 g / m 2 • For 24 hours, the air resistance index is ≥10.0×10 4 s / (in 2 (100cc, 1.22kPa), the antibacterial rate is ≥99.99%. After wet heat cycling, the moisture permeability retention rate is ≥91%, the gas barrier index retention rate is ≥92%, and the antibacterial rate retention rate is ≥90%. This indicates that the total heat exchange membrane of the present invention has good moisture permeability and gas barrier properties, good antibacterial performance, and after multiple wet heat cycles, the moisture permeability and gas barrier properties of the total heat exchange membrane are maintained well, and the antibacterial performance is also maintained well.

[0096] Comparing Examples 1, 3, and 4, it can be seen that by adjusting the viscosity of alginate within a specific range (15~250 mPa·s), the total heat exchange membrane obtained retains its various properties better after multiple wet heat cycles.

[0097] Comparing Examples 1, 6, and 7, it can be seen that by controlling the average particle size of nano-silica within a specific range (11~16nm), the obtained total heat exchange membrane has better moisture permeability and gas barrier properties.

[0098] Comparing Examples 1, 8, and 9, it can be seen that by adjusting the water contact angle of the porous support membrane surface within a specific range (60~65°), the obtained total heat exchange membrane has better moisture permeability and gas barrier properties, and the moisture permeability and gas barrier properties are also better maintained after multiple hygrothermal cycles.

[0099] Comparing Examples 1, 12, and 13, it can be seen that by adjusting the mass ratio of sodium alginate to crosslinking agent within a certain range ((4~5):(2~3)), the gas barrier properties of the obtained total heat exchange membrane are better maintained after multiple humid heat cycles.

[0100] The water contact angle on the surface of the porous support membrane in Comparative Example 1 was too high, resulting in poor moisture permeability of the obtained total heat exchange membrane. Furthermore, after multiple wet and heat cycles, the moisture permeability, gas barrier properties, and antibacterial properties were poorly maintained.

[0101] Comparative Example 2 did not add alginate, Comparative Example 3 did not add alginate and replaced it with an equal amount of polyvinyl alcohol, and Comparative Example 4 did not add alginate and replaced it with an equal amount of a commonly used thickener (sodium carboxymethyl cellulose). The total heat exchange membranes obtained by the three examples had poor moisture permeability and gas barrier properties, and after multiple wet heat cycles, the moisture permeability, gas barrier properties and antibacterial properties were poorly maintained.

[0102] Comparative Example 5, without the addition of calcium salt, resulted in a total heat exchange membrane with poor moisture permeability and gas barrier properties. Furthermore, after multiple wet and heat cycles, the retention of moisture permeability, gas barrier properties, and antibacterial properties was poor.

[0103] Comparative Example 6, which did not add calcium salt and replaced it with an equal amount of lithium salt, resulted in a total heat exchange membrane with poor gas barrier performance. After multiple humid heat cycles, the retention of moisture permeability, gas barrier performance, and antibacterial performance was poor or unsatisfactory.

[0104] Comparative Example 7, which did not add calcium salt and replaced it with an equal amount of zinc salt, produced a total heat exchange membrane with poor moisture permeability and gas barrier properties. Furthermore, after multiple wet heat cycles, the moisture permeability, gas barrier properties, and antibacterial properties were poorly maintained.

[0105] Comparative Example 8, without the addition of nano-silica, resulted in a total heat exchange membrane with poor moisture permeability and gas barrier properties.

[0106] Comparative Example 9, which did not add nano-silica and replaced it with an equal amount of micron-sized silica, resulted in a total heat exchange membrane with poor moisture permeability and gas barrier properties, and its gas barrier properties were poorly maintained after multiple hygrothermal cycles.

[0107] Comparative Example 10, which did not add nano-silica and replaced it with an equal amount of montmorillonite, produced a total heat exchange membrane with poor moisture permeability and gas barrier properties, and its gas barrier properties were poorly maintained after multiple hygrothermal cycles.

[0108] The mass ratio of polyvinyl alcohol to chitosan in Comparative Examples 11 and 12 was unsuitable, resulting in poor moisture permeability and gas barrier properties of the obtained total heat exchange membranes. Furthermore, after multiple hygrothermal cycles, the retention of moisture permeability, gas barrier properties, and antibacterial properties was poor or unsatisfactory.

[0109] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A total heat exchange membrane, characterized in that, It includes a porous support membrane and an active layer loaded on the surface of the porous support membrane; By weight, the active layer comprises the following components: 0.8-2 parts polyvinyl alcohol, 0.2-0.6 parts alginate, 0.1-0.25 parts crosslinking agent, 1.6-4 parts chitosan, 0.3-1.3 parts calcium salt, 0.8-1.6 parts hygroscopic agent, 0.08-0.32 parts antibacterial agent, and 0.16-0.48 parts nano silica; The water contact angle of the surface of the porous support membrane is ≤78°.

2. The total heat exchange membrane according to claim 1, characterized in that, The porosity of the porous support membrane is 30-50%; and / or The average pore size of the porous support membrane is 0.1~0.5μm; and / or The porous support membrane can be made of one of the following materials: polypropylene, polyethylene, polyamide, polytetrafluoroethylene, and polyvinylidene fluoride. and / or The thickness of the porous support membrane is 10-20 micrometers.

3. The total heat exchange membrane according to claim 1, characterized in that, Satisfying at least one of a) to c): a) The viscosity-average molecular weight of the polyvinyl alcohol is 50,000 to 200,000; b) The viscosity of the alginate measured at 25°C, with deionized water as the solvent and a concentration of 1 wt%, is 10~1500 mPa·s; c) The weight-average molecular weight of the chitosan is 50,000 to 400,000.

4. The total heat exchange membrane according to claim 1, characterized in that, Satisfy at least one of d) to f): d) The crosslinking agent is at least one of glutaraldehyde, glyoxal, maleic acid, malic acid or polyethylene glycol diglycidyl ether; e) The calcium salt is at least one of calcium halide, calcium nitrate, calcium lactate, or calcium gluconate; f) The antibacterial agent is at least one of zinc oxide or elemental silver; g) The hygroscopic agent is at least one of lithium chloride, zinc chloride, and nano-montmorillonite.

5. The total heat exchange membrane according to claim 1, characterized in that, The thickness of the active layer is 1~5μm.

6. The total heat exchange membrane according to claim 1, characterized in that, The mass ratio of alginate to crosslinking agent is (8~11):(3~6).

7. The total heat exchange membrane according to claim 1, characterized in that, The surface of the nano-silica is modified with a silane coupling agent; preferably, the silane coupling agent is at least one selected from γ-aminopropyltriethoxysilane, N-β-aminoethyl-γ-aminopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, and mercaptopropyltrimethoxysilane.

8. The method for preparing the total heat exchange membrane according to any one of claims 1 to 7, characterized in that, Includes the following steps: The components of the active layer are prepared into a casting solution, which is then coated onto the surface of a porous support membrane and dried to form the active layer, thus obtaining the total heat exchange membrane.

9. The use of the total heat exchange membrane according to any one of claims 1 to 7 in the preparation of a total heat exchanger.

10. A total heat exchanger, characterized in that, Includes the total heat exchange membrane described in any one of claims 1 to 7.